2018
DOI: 10.2516/ogst/2018059
|View full text |Cite
|
Sign up to set email alerts
|

Study on three phase foam for Enhanced Oil Recovery in extra-low permeability reservoirs

Abstract: Poly (MSt-MMA) nanosphere as foam stabilizing agent was synthesized by emulsion polymerization. The three phase foam was prepared with Disodium 4-Dodecyl-2,4′-Oxydiben Zenesulfonate (DOZS) as foaming agent, Hydrolyzed Polyacrylamide (HPAM) and synthesized poly (MSt-MMA) nanospheres as the mixed foam stabilizing agents. It had outstanding foaming performance and foam stability. The optimal three phase foam system consisting of 0.12 wt% HPAM, 0.04 wt% poly (MSt-MMA) nanospheres and 0.12 wt% DOZS by orthogonal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, the success of foam flooding depends strongly on foam stability (Amirmoshiri et al, 2018; Jian et al, 2015; Wang et al, 2019; Yang et al, 2017; Yekeen et al, 2017), which is correlated with the liquid drainage in lamellae, surface dilatational elasticity, and strength of the surfactant films (lamellae) (Wang et al, 2009), whereas the foam stability in porous medium is affected by several factors, including temperature, pressure, surfactants used, the presence of oils, electrolytes, polymers, and solid particulate materials (Chen et al, 2018; Hurtado et al, 2018). Many improved foaming systems for foam flooding have been reported in which the protocols for increasing foam stability include addition of nanoparticles (Bashir et al, 2019; Hurtado et al, 2018; Lu et al, 2017; Manan et al, 2015; Rezvani et al, 2020; Risal et al, 2018; Xu et al, 2020; Yang et al, 2017; Yekeen et al, 2017; Zhou et al, 2018), polymers (Bai et al, 2019; Jian et al, 2015; Sun et al, 2015a; Zhu et al, 2004), and alcohols (Chen and Zhao, 2015) and use of mixed surfactants (Hosseini‐Nasab and Zitha, 2017; Wang et al, 2016), branched surfactants (Wang et al, 2009), and fluorine‐containing surfactants (Jian et al, 2015; Wang et al, 2016) etc .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the success of foam flooding depends strongly on foam stability (Amirmoshiri et al, 2018; Jian et al, 2015; Wang et al, 2019; Yang et al, 2017; Yekeen et al, 2017), which is correlated with the liquid drainage in lamellae, surface dilatational elasticity, and strength of the surfactant films (lamellae) (Wang et al, 2009), whereas the foam stability in porous medium is affected by several factors, including temperature, pressure, surfactants used, the presence of oils, electrolytes, polymers, and solid particulate materials (Chen et al, 2018; Hurtado et al, 2018). Many improved foaming systems for foam flooding have been reported in which the protocols for increasing foam stability include addition of nanoparticles (Bashir et al, 2019; Hurtado et al, 2018; Lu et al, 2017; Manan et al, 2015; Rezvani et al, 2020; Risal et al, 2018; Xu et al, 2020; Yang et al, 2017; Yekeen et al, 2017; Zhou et al, 2018), polymers (Bai et al, 2019; Jian et al, 2015; Sun et al, 2015a; Zhu et al, 2004), and alcohols (Chen and Zhao, 2015) and use of mixed surfactants (Hosseini‐Nasab and Zitha, 2017; Wang et al, 2016), branched surfactants (Wang et al, 2009), and fluorine‐containing surfactants (Jian et al, 2015; Wang et al, 2016) etc .…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors to damage foam stability, the presence of oils is usually detrimental (Amirmoshiri et al, 2018; Chen et al, 2018; Hussain et al, 2019; Pu et al, 2019), which usually behave as excellent defoamers, although positive role of the oils to foam stability has also been reported when they are trapped in foam lamellae as emulsified oil droplets (Pu et al, 2019). As for the relationship between foam stability and oil displacement efficiency, some studies concluded that foam stability was not a necessary requirement in EOR (Pu et al, 2019) and no correlation between bulk foam stability and displacement efficiency was observed (Amirmoshiri et al, 2018), but more studies insisted that foams with high stability are in favor of enhancing oil recovery (Bai et al, 2019; Bashir et al, 2019; Chen and Zhao, 2015; Hosseini‐Nasab and Zitha, 2017; Hurtado et al, 2018; Jian et al, 2015; Lu et al, 2017; Manan et al, 2015; Pu et al, 2019; Rezvani et al, 2020; Risal et al, 2018; Sun et al, 2015; Wang et al, 2009, 2016; Xu et al, 2020; Zhang et al, 2019; Zhou et al, 2018; Zhu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the remaining oil mainly exists in medium-low permeability reservoirs. While these reservoirs are always bad in physical properties and the distribution of remaining oil is relatively dispersed, it is difficult to inject the oil displacement agent and, definitely, the remaining oil is difficult to be produced [10,11]. Therefore, there is an urgent need for a reasonable oil formation improvement method that can effectively produce the oil and release the dispersed remaining oil.…”
Section: Introductionmentioning
confidence: 99%
“…[6]. Presently, although there are two means (One is chemical and the other is mechanical) to decrease the excess water production, only the chemical methods can play a treatment role in the depths of the stratum, so that the chemical methods are widely used to increase oil production and decrease water cut in heterogeneous reservoirs around the world [7][8][9]. Among the many chemical methods, a polymer gel for conformance control and water shutoff is the most widely used due to a good adaptability and a low price [10].…”
Section: Introductionmentioning
confidence: 99%